Ubit' 6 iiulia 1918 god . To Kill on 6 July, 1918 - Razdorskii, Stanislav (NTV, 2001)
The episode narrates the story behind the assasination of Mierbach, the German Ambassador to Russia, which took place on 6 July, 1918, and the involvment of the French and Soviet secret services in carrying out the plan.